2010
DOI: 10.3945/jn.109.120584
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Starch Digestion Kinetics, Corrected for Estimated Gastric Emptying, Predict Portal Glucose Appearance in Pigs ,

Abstract: In vitro starch digestion is used for predicting the in vivo glucose response, but their relationship has not been defined thoroughly. To clarify, in vitro starch digestion using a modified Englyst-assay was compared to portal glucose appearance in pigs. Four portal vein-catheterized pigs (43.2 +/- 4.8 kg body weight) were fed 4 diets containing 70% purified starch ranging from slowly to rapidly digestible [maximal rate of in vitro digestion (%)/min: 0.22 (slowly), 0.38, 0.73, and 1.06 (rapidly)] for 7-d perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 29 publications
6
59
0
Order By: Relevance
“…Consequently, assuming that the mean retention time of digesta through the small gut of pigs with conventional diets is around 4 h (Wilfart et al, 2007), a time of 240 min has been considered for the estimation of potential amylolytic activity, and SDS and RS have been calculated accordingly. Thus, our results for RDS, SDS and RS agreed well with those expected from results of Sun et al (2006) and Van Kempen et al (2010), showing that P and R diets promote the highest and lowest proportion of potentially fermentable starch to the hindgut, respectively.…”
Section: Resultssupporting
confidence: 79%
“…Consequently, assuming that the mean retention time of digesta through the small gut of pigs with conventional diets is around 4 h (Wilfart et al, 2007), a time of 240 min has been considered for the estimation of potential amylolytic activity, and SDS and RS have been calculated accordingly. Thus, our results for RDS, SDS and RS agreed well with those expected from results of Sun et al (2006) and Van Kempen et al (2010), showing that P and R diets promote the highest and lowest proportion of potentially fermentable starch to the hindgut, respectively.…”
Section: Resultssupporting
confidence: 79%
“…Crude fat content was determined by extraction with ether (method 920.39; AOAC, 1990) using a Goldfisch Fat Extractor (Laconco). The starches were considered rapidly digestible (S1), moderately rapid digestible (S2), moderately slow digestible (S3), and slowly digestible (S4) based on the maximum rate of in vitro starch digestion based on a 2-stage in vitro digestion assay modified after Englyst [S1, 1.06; S2, 0.73; S3, 0.38; and S4, 0.22%/min (10)]. …”
Section: Methodsmentioning
confidence: 99%
“…The in vitro Englyst method for mimicking digestion in the human gastrointestinal tract was employed in this study (14). A study with pigs showed that the digestion of starch fractions in vitro was strongly associated with glucose occurrence in the portal vein in a similar experiment conducted in vivo and corrected for predicted gastric emptying (38). In a study with young human adults, the glycemic response to maltodextrin, whole grain, high-amylose, and regular corn starches was strongly correlated with in vitro estimates of their digestibility (3).…”
Section: Discussionmentioning
confidence: 99%
“…This process was repeated for all the samples at 30 sec intervals to facilitate the timing of the procedure. The incubation period was a total of 180 min; 0.5 mL aliquots of sample were removed from each of the tubes at exactly 0, 15, 30, 45, 60, 90, 120, 150, and 180 min and transferred into smaller 25 mL screw-cap tubes filled with 4 mL of absolute alcohol to stop enzymatic hydrolysis (38). The transferred samples were centrifuged at 1500g, and the supernatants were aliquoted and stored in the freezer at -18°C.…”
Section: Methodsmentioning
confidence: 99%